Influence of Ballhandling Techniques on the Ball Mastery Skills of Students in Basketball Games at SMA Negeri 17 Garut - Nurparisi, Muhammad Luthfi; Kurniawati, Ani; Arifin, Z.; Permadi, Asep Angga (Musamus Journal of Physical Education and Sport (MJPES), 2024)
The development of physical education learning is a systematic process that facilitates the effective and efficient formation of a complete individual by managing the interaction between students, educators, and the environment. Objective. The purpose of this investigation was to ascertain the impact of ball modification on the capabilities of SMAN 17 Garut. Materials and Methods. The Quasi-Experimental research procedure was implemented in this investigation. Ballhandling training is a technique that is used to facilitate the communication of a learning process or to establish learning objectives for students. It can be modified to include game forms, tools, and other learning processes. The sample in this research consisted of 42 students, while the population consisted of all students at SMAN 17 Garut. Purposive sampling techniques were implemented in this investigation. The author employed observation to gather data on the dribbling abilities of students. Results. The data analysis test concluded that the impact of ball modification on the results of fundamental movements and students' playing in football, basketball, and volleyball games of SMAN 17 Garut students was 7.3%. A total of 42 pupils exhibited a substantial impact. Conclusion. The study's conclusion is that the modification of learning instruments and methods can enhance the effectiveness of systematically designed physical education. At SMAN 17 Garut, ball modifications have been demonstrated to have a substantial and beneficial impact on the enhancement of fundamental playing skills, particularly in the area of agility, for soccer, basketball, and volleyball games. This effect is evident in the observations of students who are participating in the study. It is recommended that additional researchers investigate additional variables that influence physical abilities, including psychological factors and motivation. It is also crucial to increase the population by involving additional institutions. Furthermore, research can evaluate the duration and intensity of training, as well as the integration of a variety of learning methodologies. It is also strongly advised to conduct a long-term assessment of the effects of ball modifications and an analysis of the types of instruments used. Lastly, student interviews can offer supplementary information regarding their learning experiences.